Analyzing the Effect of “Size” and “Export Experience” Factors on Perceived Obstacles of Exports Administrative - Service Activities A Case Study of North-East Cooperatives of Iran - S Nazemi; A Shirazi; D Khani (تعاون و کشاورزی, 2011)
Over two decades ago, along with global economic growth, export is considered as an economic activity that had more growth than other activities. Also at the corporate level, exports is considered as a possibility for more sales, profitability and economy of scale to reduce product development costs and ultimately increase the standard of living for customers and improve the quality of work life for employees. After marketing, production and preparation and of goods (commercial process), firms transacts with various governmental and private agencies (such as customs, standards organization, trade organizations, chambers of commerce, transportation companies etc.) to complete export process and exit the country. This part of the activities of exporting may be grouped under "administrative – Service" factors. This study analyzes the effect of the "export experience" and "Organizational size" on the obstacles of different activities of "administrative-service" process from the viewpoint if exporters. In other words exporter’s evaluations of the total expenses of "administrative – Service" activities ranging from labor costs, time and financial costs will be questioned and this issue evaluate that whether or not significant differences in perceived obstacles will be obtained by changing "size" and "experience" factor. Research population consists of all cooperatives located in the provinces of "Khorasan Razavi" and "North Khorasan". Research method of descriptive and analytical survey utilized a random sampling plan, resulted in 54 samples from a total of 350 manufacturing firms. In order to collect research data, a designed questionnaire was designed by referring to library resources, organizations are in charge of exports administrative-service affairs, expert exporters’ organization and academic instructors. Appropriate technique was incorporated to assure validity of the instrument, and its reliability was also confirmed by a Cronbach's alpha coefficient of 0.84. Descriptive statistics and inferential statistics (nonparametric tests) were used to test hypotheses by SPSS software. 'Kruskal-Wallis' test used for analyzing the "export experience" effect on the obstacles of "administrative – Service" activities. Also ' Mann-Whitney' test used for analyzing the "Organization size" effect on the obstacles of these activities. With some nonparametric tests, it was found that, "currency transfer by exchange centers and peoples" and "settling claims" processes appear to play decreased role as exports experiences increase. On the other hand the “organization size” has no effect on changing perceived obstacles of administrative-service export activities.